'A vision for the future': Professional ethos as boundary work in Mozambique's public sector. (December 2022) - Schubert, Jon
Global imaginaries of middle-classness, although resonating in very different ways in specific national contexts, more often than not conform to broadly capitalist-liberal aspirations, through globalised markers of consumption and individual social advancement. However, as this ethnographic material from Mozambique's mining and hydrocarbons sector suggests, even under contemporary conditions of neoliberalism, alternative imaginings of middle-classness, based on technical competence, cosmopolitanism, work ethos and professionalism as contributing to a larger narrative of national progress persist as echoes of socialist technical assistance among the technocrats managing the sector. This article explores how professionalism is constructed across regime changes, from a socialist, high modernist socio-political project that has all but vanished today as a global emancipatory reference, to the current, neoliberal economic and political dispensation that requires of public administrators to promote a business-friendly climate. Professionalism, I show, cuts across generations despite considerable differences, indexing this class's shifting claims on the state.